Interactions of Circadian Rhythmicity, Stress and Orexigenic Neuropeptide Systems: Implications for Food Intake Control - Blasiak, Anna; Gundlach, Andrew L.; Hess, Grzegorz; Lewandowski, Marian H. (Frontiers in Neuroscience, 2017)
Many physiological processes fluctuate throughout the day/night and daily fluctuations are observed in brain and peripheral levels of several hormones, neuropeptides and transmitters. In turn, mediators under the ‘control’ of the ‘master biological clock’, reciprocally influence its function. Dysregulation in the rhythmicity of hormone release as well as hormone receptor sensitivity and availability in different tissues, is a common risk-factor for multiple clinical conditions, including psychiatric and metabolic disorders. At the same time circadian rhythms remain in a strong, reciprocal interaction with the hypothalamic-pituitary-adrenal (HPA) axis. Recent findings point to a role of circadian disturbances and excessive stress in the development of obesity and related food consumption and metabolism abnormalities, which constitute a major health problem worldwide. Appetite, food intake and energy balance are under the influence of several brain neuropeptides, including the orexigenic agouti-related peptide, neuropeptide Y, orexin, melanin-concentrating hormone and relaxin-3. Importantly, orexigenic neuropeptide neurons remain under the control of the circadian timing system and are highly sensitive to various stressors, therefore the potential neuronal mechanisms through which disturbances in the daily rhythmicity and stress-related mediator levels contribute to food intake abnormalities rely on reciprocal interactions between these elements.